RAMADAN AND PSYCHOSOCIAL WELL-BEING: IMPLICATIONS FOR MENTAL HEALTH POLICY IN EDUCATIONAL SETTINGS - Hadiansyah, Andri; Fahmi, Ahmad Rosikhul; Gymnastiar, Iman Ahmad; Nugroho, Feby Arief; Farid, Fadlyansyah (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
This literature review explores the relationship between Ramadan observance and psychosocial well-being, with a particular emphasis on its implications for mental health policy within educational environments. Drawing upon a systematic evaluation of existing scholarly literature, this study identifies key psychosocial dimensions positively influenced by Ramadan, including enhanced self-regulation, resilience, and social connectedness among students. The evidence indicates that Ramadan fasting and associated spiritual practices can significantly mitigate stress, anxiety, and depressive symptoms, thereby contributing to improved overall mental health outcomes. However, the review also highlights variations in psychosocial impacts based on cultural contexts, institutional support systems, and individual differences in religious commitment. Importantly, educational institutions often lack clear policies to support students effectively during Ramadan, potentially undermining the observed psychosocial benefits. This review underscores the necessity for culturally sensitive mental health policies that accommodate Ramadan-related practices, facilitating supportive environments for students observing the fasting month. Effective implementation of such policies would require collaborative efforts among educational policymakers, mental health professionals, and community leaders. Limitations inherent in the reviewed studies, such as methodological heterogeneity and context-specific outcomes, are also acknowledged, reinforcing the need for further rigorous research. Consequently, this article provides foundational insights for educational policymakers aiming to optimize psychosocial well-being through evidence-based interventions aligned with Ramadan practices.